The socio demographic profile and other characteristics of adult burns patients treated at Johannesburg tertiary hospitals - Ncedani, Andiswa (My University, 2014)
Introduction: This is the descriptive study of the socio demographic profile and other characteristics such as the burn injury details and socio economic characteristics of adult burn injury patients treated at Johannesburg Tertiary Hospitals (JTH) during the study period. Relevant stakeholders can use this information in the efforts to reduce preventable burn injuries. Method: Prospective study where all adult burn patients in the burns unit, trauma/surgical wards during the study period were eligible to participate in the study. The information was extracted from the medical files (such as hospital classification, date of birth (DOB), type of burn, type of management done to date etc), this was followed by an interview done by principal investigator only, using a questionnaire to gather the information on patients’ demographic details, socio economic information, income details and burn injury details. Descriptive statistics were used to define the profile of burn patients and other characteristics. Results: The results revealed the description and the profile of adult burn patients: a male (71%), African (94%), unmarried (70%), mean age of 35.6 years. He was most likely to have a secondary school qualification (62%), full time employed possible (51%) in the industrial sector, stays with 2-5 people in his household. He was likely to be originally from outside the Gauteng Province (58%). He sustained burns injuries of 10-29% TBSA, while at home (94%), from flames (68%). He remembered (92%), his activity prior to the burn incident and thought that the burn could have been prevented (82%). Conclusion: Burns injuries were reported to be preventable. The burn injury-prevention program should be targeted to males, in the working age groups, residing in one roomed dwelling or informal settlements. Patients with poor judgement, predisposing medical conditions such as epileptics, those that have modified their electricity supply and heat sources should be prioritised for burn injury-prevention programs.
The research report is submitted to the School of Public Health, Faculty of Health Sciences, University of Witwatersrand, in partial fulfilment of the requirements for the Master of Public Health degree. Johannesburg March, 2014
Keywords: Socioeconomic Factors; Burns; Disaster Victims